Text and image : a critical introduction to the visual/verbal divide - Bateman, John A. (London : Routledge, 2014)
'This introductory textbook explores and analyses the various approaches to multimodality and offers the first comprehensive, in-depth survey of all aspects of the text-image relation.The text-image relationship has long been a cornerstone of diverse approaches to multimodality and there are many different accounts. This book leads students into each of the approaches discussed, brings out their strengths and weaknesses using illustrative example analyses and includes exercises and research questions to reinforce learning. Throughout the book, John Bateman looks at a wide range of perspectives: socio-semiotics, visual communication, psycholinguistic approaches to discourse, rhetorical approaches to advertising and visual persuasion, and cognitive metaphor theory. Applications of the styles of analyses presented are discussed for a variety of materials, including textbooks, PowerPoint presentations, picture books, technical manuals and comics. Requiring no prior knowledge of the area, this is an accessible text for all students studying text and image or multimodality within English language and linguistics, media and communication studies, visual and design studies'--
Includes bibliographical references (pages 251-267) and index.
Keywords: Modality (Linguistics).; Visual communication -- Psychological aspects; Discourse analysis -- Psychological aspects; Semiotics; Rhetoric; Psycholinguistics